Narratives of Referral Experiences for Maternal, Newborn, and Child Health Complications in Mozambique, Nampula Province Findings from a Qualitative Study - COWI; USAID; MISAU (2019)
As part of its family-centered systems approach, MCSP supported the Nampula Provincial Health Directorate to develop operational guidelines, including registers and reporting tools. These resources enabled the establishment of eight functional referral networks covering all facilities in Nampula to improve provision of integrated care with effective referral/counter referrals for reproductive, maternal, newborn and child health care, including emergency complications and ambulatory referrals. MCSP/Mozambique collected qualitative information from women in Nampula who had experienced a referral. These referral narratives were then studied to: 1) better understand the experiences of women in Nampula Province who were referred to a health facility for themselves or their children due to a health complication; and 2) examine the factors contributing to whether and how those referrals were completed.